From Best to Intentional Practices: Reimagining Implementation of Gender-Inclusive Housing. Issue 2 (3rd April 2018) - Nicolazzo, Z; Marine, Susan B.; Wagner, Rachel
Abstract : Using findings from a national study of trans* students' experiences in gender-inclusive housing, we argue student affairs educators must move toward gender-inclusive housing as an intentional—rather than best—practice. We frame this innovation in the practice of gender-inclusive housing through findings related to the need to perform ongoing assessment regarding these housing options as well as challenging the conceptualization of gender-inclusive housing in ways that center cisgender staff members' fears and feelings.